Upaya Pencegahan dan Penanggulangan Kasus Perkosaan Secara Berkelompok (Gang Rape) Yang Dihentikan Penyidikannya Dengan Alasan Restorative Justice - Reynaldy Vallentino Lily Lamma; Reny Rebeka Masu; Rudepel Petrus Leo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The application of restorative justice in cases of sexual violence in Indonesia actually has the potential to cause major losses for victims, resulting in victims not getting the right to recovery for what they experienced and the perpetrators being free from responsibility for the criminal punishment they should receive. This research aims to find out and explain efforts that can be made to prevent and overcome the recurrence of gang rape cases whose investigations have been stopped for reasons of restorative justice. The research method used is Normative Law research which obtains data from secondary data consisting of primary legal material, secondary legal material and tertiary legal material, with systematic identification of Legal Norms. The research results show that the practice of marrying the perpetrator to the victim in rape cases is often considered a form of restorative justice. In fact, the application of restorative justice in cases of sexual violence in Indonesia actually has the potential to cause major losses for the victim. As a result, victims do not get the right to recovery for what they experienced and the perpetrators are free from responsibility for the criminal punishment they should receive. Using crime prevention theory, it was found that the criminal justice process is the key to providing a deterrent effect to criminals or to people who have the potential to commit the same crime, so this process must be carried out well so that the application of criminal law can have an impact on not repeating the same criminal act. by the perpetrator. Settlement of sexual violence cases using peace mechanisms or marrying the victim to the perpetrator is completely unjustified and will always be detrimental to the victim. If victims do not receive the justice they hope for, more victims of sexual violence will be reluctant to resolve their cases through law enforcement mechanisms. It is hoped that the government, especially law enforcement officials, will need to evaluate the provisions for implementing restorative justice in cases of sexual violence and revise technical regulations that strengthen protection and recovery for victims.